Social media, criminal law, and legality - Higson-Bliss, Laura (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"Utilising Lon Fuller's conception of legality, this book argues that current legal provisions often used to control online abuse aided by social media do not conform to the basic principles of legality in the criminal law, in turn, threatening freedom of expression. How we regulate inappropriate behaviour online, often referred to as online abuse, particularly online abuse aided by social media, is a contemporary concern for governments across the globe. Tragedies, such as the death of a celebrity following a campaign of online abuse, often hit the headlines, followed by the same echo: 'there should be a law against this'. Yet, in England and Wales, numerous laws exist to control, prosecute and convict individuals who use the likes of social media to harass, intimidate and abuse others online. So why is the law failing to keep pace with modern technology? This monograph critically examines this fundamental question, from the perspective of legality. Applying criminal law to three growing areas of concern, it covers: (1) racist speech, (2) cyber harassment/stalking and (3) the sending of abusive messages online. It then turns to examine the latest attempts by the UK Government to tackle these issues through the implementation of the Online Safety Act 2023 and France's, Germany's, and India's attempts to regulate social media. The book will be of interest to researchers in the field of criminal law and cyber law, as well as online abuse, harassment and discrimination"--
Freedom of expression : the online context -- Regulating social media : theoretical positioning -- Online racism and the criminal law -- Harassment and stalking online -- Abusive communications online : the development of communication law -- The future of communication law -- Regulating online behaviour in the UK : beyond the criminal -- International perspectives on social media and the law.
Keywords: Fuller, Lon L. -- 1902-1978.; Computer crimes -- Law and legislation -- Great Britain; Social media -- Law and legislation -- Great Britain -- Criminal provisions; Online social networks -- Law and legislation -- Great Britain -- Criminal provisions; Hate speech -- Law and legislation -- Great Britain; Cyberbullying -- Law and legislation -- Great Britain; Freedom of expression -- Great Britain; Social media -- Law and legislation; LAW / Computer & Internet; LAW / Criminal Law / General; LAW / Communications